Triumph on Everest : a photobiography of Sir Edmund Hillary - Coburn, Broughton, 1951- (Washington, D.C. : National Geographic Society, 2003)
A biography of Edmund Hillary, whose love of snow, mountains, and the outdoor life culminated in his conquering the highest peak in the world.
Includes bibliographical references (p. 63) and index.
7.4
5-8
5-8
Wilson's Children
School Library Journal
Keywords: Hillary, Edmund, -- 1919-2008 -- Juvenile literature; Mountaineers -- New Zealand -- Biography -- Juvenile literature; Hillary, Edmund, -- 1919-2008 -- Pictorial works -- Juvenile literature; Mountaineering -- Everest, Mount (China and Nepal) -- Juvenile literature; Hillary, Edmund, -- 1919-2008.; Mountaineers; Mountaineering; Everest, Mount (China and Nepal); Hillary, Edmund, -- 1919-2008.; Mountaineers -- Biography; Mountaineering; Everest, Mount (China and Nepal)